2008
DOI: 10.1038/bmt.2008.95
|View full text |Cite
|
Sign up to set email alerts
|

The role of maintenance chemotherapy after autotransplantation for acute lymphoblastic leukemia in first remission: single-center experience of 100 patients

Abstract: A total of 100 adults with ALL in first CR received melphalan (110 mg/m 2 ) with TBI followed by autologous marrow (n ¼ 35) or single-agent melphalan (200 mg/m 2 ) followed by autologous blood stem cells (n ¼ 65). After adequate hematologic recovery, maintenance chemotherapy with 6-mercaptopurine, methotrexate and vincristine-prednisone was administered for 2 years. Six patients, all TBI recipients (P ¼ 0.001), died of toxicity. In total 70 patients received 6-mercaptopurine, 53 received methotrexate and 40 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…[ 12 ] Similarly, Sirohi et al . [ 13 ] and Mehta et al . [ 14 ] also found that maintenance chemotherapy after auto-HSCT could diminish the relapse rate as well as improve the prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…[ 12 ] Similarly, Sirohi et al . [ 13 ] and Mehta et al . [ 14 ] also found that maintenance chemotherapy after auto-HSCT could diminish the relapse rate as well as improve the prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…The 7-year probabilities of DFS for patients receiving zero, one, two and three maintenance chemotherapy agents were 15%, 29%, 58% and 61%, respectively (P ¼ 0.0001). 34 Only four prospective studies designed patients to receive maintenance therapy after auto-SCT, 4,6,7,10 and only 12 --52% patients actually took maintenance therapy. This may lead to an underestimation of the real potency of auto-SCT.…”
Section: Discussionmentioning
confidence: 99%
“…The preponderance of evidence shows that there were no differences in outcomes between these groups. Other studies [27,28] have demonstrated that long-term maintenance chemotherapy remains a critical component to achieve the best possible outcome even for patients undergoing high-dose therapy followed by auto-HCT.…”
Section: Trials Comparing Chemotherapy With Allo-hematopoietic Cell Tmentioning
confidence: 99%